Strategi Tokoh Lokal melalui Komunitas Singo Gendeng dalam Memberdayakan Pengemis Anak - Fida Anisah Restanti; Nur Dyah Gianawati; Wahyuni Mayangsari (University of Jember, 2023)
Beggars have become the main problem in various regions, especially in urban slum areas due to the poverty conditions in their environment. One of the villages located in the Talangsari area in the Jember Kidul Village, which is often stigmatized by the local community by the nickname